WRITING PROCEDURE TEXT BY USING TEAM PAIR SOLO TECHNIQUE - Nabujing, Nurul Hidayah; Utari, Putri (EXCELLENCE: Journal of English and English Education, 2023)
This article elaborate the teaching of writing procedure text by using team pair solo technique. The steps or procedures of using this technique are described thoroughly. This technique can be one option for the teachers to assist them in teaching learning writing of English.